Clinical Evaluation of Herbal Medicine (ICH-012) in Treating Acute Cerebral Haemorrhage: Safety and Efficacy from 6- to 72-Hour Time Window (CRRICHTrial-II). (26th August 2018) - Zhang, Qixin; Zeng, Liling; Chen, Xiuyan; Zhou, Yuexiang; Gong, Baoying; Li, Haijun; Guo, Jianwen
Abstract : Background . Hypertensive intracerebral haemorrhage (HICH), which is characterized by rapid change, high morbidity, and mortality, is extremely dangerous. Both medical and surgical treatments lack definitive evidence and remain controversial. A prospective RCT that we have conducted has shown that the usage of the herbal medicine ICH-012 within 6 h of the event may increase the risk of haematoma enlargement and gastrointestinal bleeding. However, the volume of haematoma remains stable after 6 h. Thus, we will increase the time window to the period from 6 to 72 h after onset to evaluate the safety and efficacy of ICH-012 treating ICH (ClinicalTrial.gov ID: NCT03354026 ). Methods/Design . The CRRICHTrial-II study, a prospective, double-blinded, controlled, multicentre RCT, includes three groups: A, B, and C. Group A patients were treated with 8 herbal medicines (with 2 herbal medicines of Hirudo and Tabanus as well as 6 other combined herbal medicines of Group B) and Group C were placebo. Patients should meet all the inclusion criteria: age between 18 and 80 and diagnosis of HICH by brain CT scan between 6 and 72 h from the onset. The CT scan will be taken at four critical time points: baseline, between 6 and 72h, 24h after onset, and between 10 and 14 days after onset. The drug intervention lasts 10 days, and there is a follow-up visit taken after 90 days. The haematoma enlargement after 24 h onset as demonstrated by CT is the primary outcome. Discussion . A large amount of data from high-quality RCTs is needed for the extensive clinical application of herbal medicine. The CRRICHTrial-II will evaluate the safety and effectiveness of ICH-012 in a safer time window between 6 and 72 h and investigate the possible mechanisms of action and direction of herbal medicine in the haematoma growth after HICH. Trial registration at ClinicalTrial.gov, ID: NCT03354026, is registered on 23rd Nov. 2017.